An introduction to the making and meaning of the Bible - Shepherd, Michael B. (Eerdmans, 2024)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- List of Tables -- Preface -- List of Abbreviations -- Introduction -- 1. The Making of the Bible -- 2. Text, Transmission, and Translation -- 3. The Meaning of the Bible in the Compositional Strategy of the Hebrew Bible -- 4. The Meaning of the Bible in the Compositional Strategy of the New Testament -- 5. The Textual World of the Bible -- Glossary -- Selected Bibliography.